Checklist, Indeks Ekologi, dan Status Konservasi Komunitas Fauna Akuatik di Kawasan Sungai Unda dan Sekitar Pantai Jumpai, Kabupaten Klungkung, Provinsi Bali - Gede Surya Indrawan; Putu Angga Wiradana; I Made Saka Wijaya; Abd. Rahman As-syakur; M. Rheza Rizki Syahputra; I Made Sara Wijana (Environmental Research Center (PPLH) of Udayana University, 2021)
Aquatic organisms or nekton have an important role in supporting the stability of the aquatic environment and human life. This study aims to determine the nekton type community, ecological index, and their conservation status in the Unda River area and around Jumpai Beach, Klungkung Regency, Bali. The study was conducted in July - August 2020. The study was conducted in 2 communities, namely Macrozoobenthos and Nekton. Macrozoobenthos samples were collected using the quadratic method in the Jumpai Beach area and the direct observation method along the Unda River. Nekton communities are collected through primary data using